The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/sciadv.1600554
|View full text |Cite
|
Sign up to set email alerts
|

Pollen tube contents initiate ovule enlargement and enhance seed coat development without fertilization

Abstract: A new plant ovule enlargement triggered by pollen tube contents, accompanied by seed coat initiation without fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 32 publications
2
38
1
1
Order By: Relevance
“…We then performed RNA-seq to analyze the gene expression profiles of the collected the synergid, egg, and central cells in the wild type and the synergid cells in the myb98 mutant (Figure 5D). RNA-seq data from these female gametophyte cells were mapped to the genome of Arabidopsis (TAIR version 10) with the published sequence data from the ovules at 12 hr-after-emasculation (HAE) (Kasahara et al, 2016) and 2-week-old seedlings (Rogers et al, 2012). There were 4,996–18,432 genes (read counts > 10) detected in each sample (Figure 6A; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…We then performed RNA-seq to analyze the gene expression profiles of the collected the synergid, egg, and central cells in the wild type and the synergid cells in the myb98 mutant (Figure 5D). RNA-seq data from these female gametophyte cells were mapped to the genome of Arabidopsis (TAIR version 10) with the published sequence data from the ovules at 12 hr-after-emasculation (HAE) (Kasahara et al, 2016) and 2-week-old seedlings (Rogers et al, 2012). There were 4,996–18,432 genes (read counts > 10) detected in each sample (Figure 6A; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…In angiosperms, the pollen tube releases its contents (including sperm cells) into the embryo sac upon insertion into the ovule, thus completing double fertilization. Recently, Kasahara et al [41,42] reported that the expansion and initiation of seed coat formation occurred even in ovules wherein fertilization failed after pollen tube insertion. This phenomenon was designated as pollen tube-dependent ovule enlargement morphology (POEM), which occurs only when the ovule accepts the pollen tube content (PTC).…”
Section: Pollen Tube-dependent Ovule Enlargement Morphology (Poem)mentioning
confidence: 99%
“…Interestingly, ovules that accepted PTC expanded without fertilization because of cell expansion and division and the production of a partial seed coat, consistent with the results of the transcriptome analysis. Using data from the successful transcriptome analysis, Kasahara et al identified that the novel plant phenomenon POEM occurs only when the ovule accepts PTC, irrespective of fertilization (Figure 7) [41].…”
Section: Pollen Tube-dependent Ovule Enlargement Morphology (Poem)mentioning
confidence: 99%
“…For instance, it was reported that release of sperm cells from the pollen tubes into the embryo sac, no matter whether fertilization is achieved or not, could trigger the division of the central cell, but endosperm development required incorporation of parental genome into the central cell (Aw et al 2010). Recently, by using a sperm cell-associated fertilization defective mutant gcs1þ/À (Mori et al 2006;von Besser et al 2006), Kasahara and his colleagues demonstrated that materials released from the pollen tubes could trigger the ovule enlargement independent of double fertilization (Kasahara et al 2016), and supported the previous conclusion that central cell division requires sperm cell entry into the embryo sac (Aw et al 2010). However, because gcs1pollen tubes, similar to the wild-type (WT) pollen tubes, contain both the cytosol of pollen tube and two sperm cells (Mori et al 2006;von Besser et al 2006), it still remains unsolved whether the signal(s) to initiate ovule enlargement are from the pollen tube or from the sperm cells.…”
mentioning
confidence: 99%